The platelet receptor CLEC-2 blocks neutrophil mediated hepatic recovery in acetaminophen induced acute liver failure - Abhishek Chauhan (Nature Portfolio, 2020)
The molecular mechanisms that drive irreversible acute liver failure remain poorly characterized. Here, the authors show that the recently discovered platelet receptor CLEC-2 (C-type lectin-like receptor) perpetuates and worsens liver damage during acute liver injury by blocking restorative neutrophil driven inflammation.